The Effect of Micro, Small, and Medium Enterprises (MSMEs) on Gross Regional Domestic Product (GRDP): Evidence from Bandung Regency, Indonesia (2019–2023) - Anwar, Miftah Khaerul (Institut Agama Islam Persis Bandung, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are widely recognized as the backbone of regional economic development in Indonesia, yet empirical evidence at the regency (kabupaten) level remains relatively scarce, particularly for high-population peri-urban areas. This study examines the effect of MSMEs on Gross Regional Domestic Product (GRDP) in Bandung Regency, West Java, over the five-year period 2019–2023 a window that spans the COVID-19 economic shock and the post-pandemic recovery. Adopting a quantitative explanatory design, the study analyses annual time-series data on the number of registered MSMEs and current-price GRDP, drawn from Statistics Indonesia (BPS) and the Bandung Regency Office of Cooperatives and MSMEs. Three statistical procedures were applied: Pearson Product-Moment correlation, simple linear regression, and the t-test for coefficient significance. Results show a very strong positive correlation between MSMEs and GRDP (r = 0.961, p = 0.009) and a coefficient of determination (R²) of 0.924, indicating that approximately 92.4% of the variation in GRDP is explained by changes in the number of MSMEs. The regression coefficient (b = 1,069.998, t = 6.052 > t-t-table 2.353, p < 0.05) confirms that MSMEs have a statistically significant positive effect on GRDP. The findings reinforce the strategic role of MSMEs as a driver of regional output but also reveal a structural anomaly: the disproportionate jump in MSME registrations in 2022 (a 106.9% increase) reflects a registration-policy effect rather than organic growth, raising questions about the validity of MSME counts as proxies for productive activity. The study recommends that local governments couple MSME formalization programmers with productivity, financing, and digital-marketing support, and that future research employ quarterly or sectoral panel data to address the small-sample limitation